Systematic Identification of Suitable Reference Genes for Quantitative Real-Time PCR Analysis in Melissa officinalis L - Bharati, Rohit; Sen, Madhab Kumar; Kumar, Ram; Gupta, Aayushi; Žiarovská, Jana; Fernández-Cusimamani, Eloy; Leuner, Olga (Plants (Basel, Switzerland), 2023)
Melissa officinalis L. is well known for its lemon-scented aroma and various pharmacological properties. Despite these valuable properties, the genes involved in the biosynthetic pathways in M. officinalis are not yet well-explored when compared to other members of the mint family. For that, gene expression studies using quantitative real-time PCR (qRT-PCR) are an excellent tool. Although qRT-PCR can provide accurate results, its accuracy is highly reliant on the expression and stability of the reference gene used for normalization. Hence, selecting a suitable experiment-specific reference gene is very crucial to obtain accurate results. However, to date, there are no reports for experiment-specific reference genes in M. officinalis. Therefore, in the current study, ten commonly used reference genes were assessed for their suitability as optimal reference genes in M. officinalis under various abiotic stress conditions and different plant organs. The candidate genes were ranked based on BestKeeper, comparative ΔCt, geNorm, NormFinder, and RefFinder. Based on the results, we recommend the combination of EF-1α and GAPDH as the best reference genes to normalize gene expression studies in M. officinalis. On the contrary, HLH71 was identified as the least-performing gene. Thereafter, the reliability of the optimal gene combination was assessed by evaluating the relative gene expression of the phenylalanine ammonia lyase (PAL) gene under two elicitor treatments (gibberellic acid and jasmonic acid). PAL is a crucial gene involved directly or indirectly in the production of various economically important secondary metabolites in plants. Suitable reference genes for each experimental condition are also discussed. The findings of the current study form a basis for current and future gene expression studies in M. officinalis and other related species.
Keywords: qRT-PCR; abiotic stress; elicitor treatment; reference genes; lemon balm; gene expression